THE HOMELAND AS A LOST PARADISE: POSTCOLONIAL ASPECTS IN SELECTED POEMS BY TANURE OJAIDE - Sayed Sadek (European Scientific Journal, ESJ, 2013)
This paper deals with some of the most notable postcolonial, neocolonial, and ecological features that characterize the works of the Nigerian poet Tanure Ojaide who is best known for his cultural assertion and seriousness of attitude. It employs the theories of such leading critics as Fanon, Nkrumah, Ngugi, and others. The paper shows the poet's deep concern regarding the demise of the homeland from a utopia to a dystopia under the neo-colonial leaders. Ojaide's anti-neo-colonial project tends to restore connections with the homeland so as to maintain a larger collective national identity. It seeks to create a sense of belonging and identity out of the feeling of displacement. The paper also examines Ojaide's resistance mechanisms based on lecturing people on how to face such neo-colonial violations and to restore the golden heritage.